2005
DOI: 10.1182/blood-2004-07-2617
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial expression of E-selectin is induced by the platelet-specific chemokine platelet factor 4 through LRP in an NF-κB–dependent manner

Abstract: The involvement of platelets in the pathogenesis of atherosclerosis has recently gained much attention. Platelet factor 4 (PF4), a platelet-specific chemokine released on platelet activation, has been localized to atherosclerotic lesions, including macrophages and endothelium. In this report, we demonstrate that Eselectin, an adhesion molecule involved in atherogenesis, is up-regulated in human umbilical vein endothelial cells exposed to PF4. Induction of E-selectin RNA is time and dose dependent. Surface expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 53 publications
(79 reference statements)
2
88
0
1
Order By: Relevance
“…In addition, EMSA experiments demonstrate that PF4 treatment of HUVECs results in binding of NF-kB to its DNA-binding site already after 1 h of stimulation. 37 The angiostatic properties of angiostatin, a cleavage product of plasminogen, have also been linked with NF-kB. Chen et al 38 have analyzed the global action of angiostatin in endothelial cells.…”
Section: Nf-jb: a Mediator In Angiostatic Therapy?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, EMSA experiments demonstrate that PF4 treatment of HUVECs results in binding of NF-kB to its DNA-binding site already after 1 h of stimulation. 37 The angiostatic properties of angiostatin, a cleavage product of plasminogen, have also been linked with NF-kB. Chen et al 38 have analyzed the global action of angiostatin in endothelial cells.…”
Section: Nf-jb: a Mediator In Angiostatic Therapy?mentioning
confidence: 99%
“…49 This normalization has been correlated with upregulation in endothelial cells of ICAM-1, VCAM-1 and E-selectin. 37,50 Therefore, activation of NF-kB by angiostatic therapy has apparently not only a direct effect on endothelial cells but also an indirect effect via expression of adhesion molecules and subsequent reversal of endothelial cell anergy (Figure 1). In addition, we have recently described that galectin-1 is a receptor for anginex, and that this protein is crucial for tumor angiogenesis.…”
Section: Role Of Nf-jb In Endothelial Cell Anergymentioning
confidence: 99%
“…The presence of PF4 in macrophages and neovascular endothelium significantly correlated with lesion grade (52). Furthermore, in a recent study, Yu et al demonstrated that E-selectin, an adhesion molecule involved in atherogenesis, is up-regulated in human umbilical vein endothelial cells exposed to PF4 (53). Finally, Nassar et al showed that PF4 bound to oxidized (ox)-LDL directly, and also increased ox-LDL binding to vascular cells and macrophages, thus demonstrating an alternative mechanism by which platelet activation at sites of vascular injury may promote the accumulation of deleterious lipoproteins (54).…”
Section: Sdf-1 and Pf4mentioning
confidence: 99%
“…PF-4 is deposited on the endothelial cell surface and retained by subendothelial proteoglycan (Aidoudi & Bikfalvi, 2010). PF-4 can activate endothelial cells by stimulating E-selectin expression (Yu et al, 2005). In vitro study indicates that PF-4 inhibits apolipoprotein Bcontaining LDL catabolism and facilitates retension of LDL on cell surface (Sachais et al, 2002).…”
Section: Tight Adhesion Of Platelet To Endothelial Cell Surfacementioning
confidence: 99%